55 A DIABETES EMPOWERMENT PROGRAM FOR OLDER LATINOS AND AFRICAN AMERICANS. (1st January 2005) - Thorne, D.; Gutierrez, P.; Brown, A.; Sarkisian, C.; Keeler, E.; Norris, K.; Davidson, M.; Anderson, R. M.; Mangione, C.
Abstract : Introduction: In 2002, 18.2 million people in the U.S. (6.3% of the population) had diabetes mellitus. Due to this, patient education, self-management skills and behavior change has become a fundamental component for interventions aiming to improve diabetes management. However, more information is needed regarding the content of the discussions during such interventions. We hypothesize that the content of the discussions in a diabetes, patient-centered empowerment program, will differ between Latino and African American groups, and will be driven by participants, not the facilitator. Methods: At the end of each two hour, diabetes class (24 Latino and 13 African American), the facilitator filled out a "post-session content" form where the degree to which a topic was covered (using a scale from 1-5, 5 being the highest), with specific notation of whether the discussion focused on solutions or barriers was recorded. Nine content areas were identified: Diet, Exercise, Prescription Medications, Self-Management, Acute and Chronic Complications, Emotions experienced with DM, Health Care-Seeking Behavior and interactions with health care professionals, the impact of the Environment and Social Support in managing DM and participating in Goal Setting. These content areas were coded and qualitative analysis of the discussion content was completed using SAS software producing means and Wilcoxon Rank Sum Tests. Results: Three out of the nine content areas were initiated and led by participants in the Latino group while in the African American groups, participants directed seven out of nine content areas. Additionally, patients' preferences for working through specific aspects of diabetes disease management differed per group. Furthermore, participants in the Latino groups focused on the solutions for 4 content areas and the barriers for 5 content areas, while the African American groups focused more on the solutions for each content area relating to their diabetes management. Conclusion: These results can help facilitators understand the behavioral learning preferences' of their participants, allowing facilitators to more effectively plan and lead participant driven discussions.